2021
DOI: 10.1007/s10661-021-09311-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of climate change on the distribution of Daphne mucronata in Iran

Abstract: Bio19 with 50.5% contribution, followed by Bio8 and Bio2 with 30% and 11.4% contributions, respectively. The best Maxent model included seven variables, 4 feature types (linear, quadratic, product, and hinge), and had a test AUC value of 0.894. The current potential distribution indicated that 8% of Iran's drylands are suitable for growing D. mucronata and this area could decrease to 5.2% under representative concentration pathway (RCP) 4.5, and 3.1% under RCP 8.5 due to climate change. Our results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…The area under the curve (AUC) ranged from 0 to 1, with higher values indicating increased confidence in predictions. An AUC value <0.8 suggested low confidence, 0.8-0.9 indicated good accuracy and 0.9-1.0 represented excellent accuracy [35]. In this study, the AUC values of the 10-fold cross-validation range from 0.926 to 0.943, with a standard deviation of 0.005 and a mean of 0.933, signifying excellent accuracy.…”
Section: Maxent Modeling and Evaluationmentioning
confidence: 56%
“…The area under the curve (AUC) ranged from 0 to 1, with higher values indicating increased confidence in predictions. An AUC value <0.8 suggested low confidence, 0.8-0.9 indicated good accuracy and 0.9-1.0 represented excellent accuracy [35]. In this study, the AUC values of the 10-fold cross-validation range from 0.926 to 0.943, with a standard deviation of 0.005 and a mean of 0.933, signifying excellent accuracy.…”
Section: Maxent Modeling and Evaluationmentioning
confidence: 56%
“…Ultimately, the overall trend for the distribution of Z. nummularia is expected to decrease. Various studies support the observed pattern of changes in Z. nummularia distribution, including those conducted by Tarnian et al (2021) and Khanal et al (2022).Top of Form…”
Section: Top Of Formmentioning
confidence: 61%
“…Studies have shown that soil, topography, and solar radiation are also important factors affecting the growth of Jerusalem artichoke (Zorić et al, 2016). Unlike previous studies that were limited to the effects of climatic factors on species distribution (Zhang et al, 2020;Tarnian et al, 2021), this study considered the effects of soil (Sillero and Barbosa, 2020). Moreover, compared with the multifactor-integrated assessment method, the Maxent model can obtain the contribution of environmental factors for species and respond to the impact of each environmental factor on the species.…”
Section: Reliability Of the Modelmentioning
confidence: 99%